Metaphor of Modality in Mata Najwa Talk Show - Gabby Maureen Pricilia; Sumarsih Sumarsih (Universitas Negeri Medan, 2016)
This study investigates the metaphor of modality in Mata Najwa Talk Show on Metro TV based on SLF approach. The objectives of this study are to identify the orientation of modality used in Mata Najwa Talk Show, to describe the orientation of metaphor of modality are used, and to explain the context of situation those metaphor of modality are used. The research design used is descriptive qualitative. The data were taken from three episodes in Mata Najwa talk show about KPK. The data were collected by downloading the video of Mata Najwa talk show from the internet. The finding shows that from four types of orientation of modality, the dominant orientation used in Mata Najwa Talk Show is objective implicit. It means that the speakers use congruent form of modality dominantly while expressing their judgment and attitude. The use of metaphor of modality in Mata Najwa Talk Show realized by the use of incongruent types of expressing meaning, that is by using projecting clause, nominalization and using preposition. Keywords: metaphor, modality, orientation